Anthropometric Evaluation of Periorbital Region and Facial Projection Using Three-Dimensional Photogrammetry. Issue 8 (November 2018) - Jodeh, Diana S.; Curtis, Heather; Cray, James J.; Ford, Jonathan; Decker, Summer; Rottgers, S. Alex
Abstract : Introduction: Direct anthropometric and three-dimensional (3D) photogrammetry measurements have been used extensively in cleft/craniofacial surgery to assess morphological changes and surgical outcomes. Craniofacial procedures alter the sagittal projection of periorbital bony prominences. Mulliken described a method of measuring their projection relative to the corneal plane but is impractical in clinical practice. Three-dimensional photogrammetry may offer a solution; however, the cornea is not visualized on this. The authors propose to develop new normative measurements of facial projection relative to the pupil. Methods: Five 3D photographs were taken of 5 individuals using Vectra M5 camera. Facial projection measurements were taken of the sagittal projection of the bilateral periorbital landmarks and nasal radix relative to the pupil using Mirror 3D analysis. Standard deviations (SD) were determined for each subject and laterality. Chi-square tests confirmed all SD <1 mm. Intra and inter-rater reliability were confirmed with an intraclass correlation coefficient assessment. Results: Three male and 2 female subjects were photographed with 5 unique images. Standard deviations of repeat measures of all landmarks were <0.5 mm. Chi-square tests confirmed with statistical significance that SD for all values except for the radix was <1 mm ( P <0.05). Intrarater reliability was high for all landmarks (intraclass correlation coefficient coefficients 0.93–0.99). Inter-rater reliability was good for the lateral canthi and excellent for all others. Conclusion: This technique demonstrates repeatability with high reliability on serial photographs and is applicable to measuring surgery effects and growth on facial projection. Establishment of age-specific normative values for landmark projection will refine usage applicability in operative planning.